Description of Village Community Knowledge about Diabetes Militus - Mustain Mustain; Ikrima Rahmasari; Tri Yuniarti; Nurulshyha Md Yatim (Global Health Science Group, 2023)
Diabetes mellitus (DM), accounts for 60% of all deaths in all age groups worldwide. Because DM complications can cause blindness, kidney failure, diabetic foot (gangrene) which requires amputation, heart disease, and stroke. risk factors, symptoms, and management of this condition. The purpose of this research is to describe the Village Community's Knowledge about Diabetes Militus. Research Methods using descriptive method. The research sample consisted of 90 respondents who were randomly selected from village communities in the study area. Data collection was carried out through a questionnaire containing questions related to knowledge about diabetes mellitus, risk factors for symptoms and management related to diabetes mellitus. The results showed that most of the respondents had low knowledge about diabetes mellitus, namely 41 respondents (45.6%). Only 10 respondents (11.1%) knew about diabetes mellitus, risk factors for symptoms and management related to diabetes mellitus. Conclusion: Village community knowledge about diabetes mellitus is still low. Therefore, education efforts and more effective health campaigns are needed to increase village community knowledge about diabetes mellitus, including risk factors, symptoms, and management. This is expected to encourage rural communities to be more aware of the importance of health and prevent diabetes mellitus and the complications that can arise.